Primary aldosteronism in hypertensive patients with obstructive sleep apnea - Zhe Hu; Xin Chen (Blood Pressure)
Objective To investigate the prevalence and clinical characteristics of primary aldosteronism (PA) in patients with hypertension and obstructive sleep apnoea (OSA) in a newly established cohort, given inconsistencies in previous studies and intolerance to drug washout in some cases.Design and method A single-centre cross-sectional study enrolled 316 hypertensive patients diagnosed with OSA via polysomnography. All participants underwent PA screening, followed by confirmatory testing for positive cases. Patients with confirmed PA underwent further subtype diagnosis and were assigned to the OSA and PA group. Those unable to undergo antihypertensive drug washout but with a high clinical suspicion of PA were categorised into the OSA and suspected PA group.Results Among 316 patients, 41 (13.0%) were PA. The prevalence was 4.8% in OSA alone, and 50.0% in OSA with hypokalaemia. Compared to the OSA group, the OSA and PA group had a lower proportion of current smokers, a longer duration of hypertension, lower serum triglycerides, lower serum potassium, higher plasma aldosterone concentration, urinary aldosterone excretion, and lower renin. Multivariable logistic regression showed that the diagnosis of PA in OSA patients was positively associated with hypertension duration, and negatively associated with serum potassium levels and smoking.Conclusions PA screening may be considered in patients with hypertension and OSA; however, given the relatively low prevalence in those with OSA alone, routine screening may not be cost-effective. In contrast, the presence of hypokalaemia was strongly associated with a higher prevalence of PA, suggesting that targeted screening is warranted in this subgroup.